Comunicações de marketing nas mídias sociais: efeitos no brand equity e na intenção de compra do consumidor - Tardin, Matheus Grage (2019)
The ubiquity of everyday social media, coupled with the growth and prominence of digital, social and mobile marketing, has changed the way consumers interact with brands and share information with each other. In social media these interactions occur through content created and disseminated by companies and consumers. Thus, the objective of this paper is to evaluate the effects of these contents both in brand equity and consumer purchase intention. In order to reach the proposed objective, as well as to test the hypotheses, the methodological approach was quantitative, cross section, survey. The population chosen for the application of the research was university students. Data collection was conducted in June 2019, and a total of 322 valid responses were obtained. The proposed model was analyzed using the Structural Equation Modeling and Multi-Group Analysis. The results show that both company-generated and user generated content influence brand equity. Company-generated content, however, has a greater effect and has greater explanatory power for brand equity than user-generated content. On the other hand, the direct effects of company-generated content and user-generated content on purchase intent are not significant when the brand equity effect is considered. The results also reveal that brand equity mediates the relationship between company and user-generated content and consumer purchase intent. As a theoretical contribution it is possible to identify results that aggregated for the field that investigates the relationship between social media and the construction of brand equity and how these variables influence consumer behavior in relation to a brand. Thus, this research contributes to the theoretical framework of marketing, specifically in the areas of relationship marketing and digital marketing, by being one of the first to evaluate the joint effects of brand and consumer generated content on brand equity and purchase intention.